2003
DOI: 10.1142/s1088424603000434
|View full text |Cite
|
Sign up to set email alerts
|

Enthalpy-entropy compensation upon syn-anti conformational switching of bis-porphyrins by amines and alcohols

Abstract: Upon interaction with amine and alcohol guests, Zn-Zn and Zn-2H ethane-bridged bis-porphyrin hosts undergo dramatic conformational switching from a syn to an anti form. The thermodynamic parameters obtained exhibit excellent linear enthalpy-entropy correlations, which are distinctly different for amines and alcohols but essentially independent of the host structure. Analyses of the compensation plots reveal a more rigid complex structure and more extensive desolvation upon complexation with amines than for alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…If the T∆S and ∆H data of ZnZn‚L 2 and Zn2H‚L are plotted in such a manner, two independent linear plots are obtained. 15 Interestingly, these plots are distinguishable not by the host but by the guest type. This suggests separate complexation characteristics primarily due to the different nature of the coordination bonds formed between the amines and alcohols and the differing solvation and geometry of these ligands.…”
Section: Temperature Thermodynamics and Enthalpy-entropy Compensation...mentioning
confidence: 99%
See 1 more Smart Citation
“…If the T∆S and ∆H data of ZnZn‚L 2 and Zn2H‚L are plotted in such a manner, two independent linear plots are obtained. 15 Interestingly, these plots are distinguishable not by the host but by the guest type. This suggests separate complexation characteristics primarily due to the different nature of the coordination bonds formed between the amines and alcohols and the differing solvation and geometry of these ligands.…”
Section: Temperature Thermodynamics and Enthalpy-entropy Compensation...mentioning
confidence: 99%
“…If the T Δ S and Δ H data of ZnZn ·L 2 and Zn2H ·L are plotted in such a manner, two independent linear plots are obtained . Interestingly, these plots are distinguishable not by the host but by the guest type.…”
Section: Temperature Thermodynamics and Enthalpy−entropy Compensation...mentioning
confidence: 99%
“…188 By virtue of these rigorous experiments, the authors: (i) added significantly to fundamental knowledge of chiral induction; (ii) reported the interactions of chiral alcohols, amines, amino acid esters; (iii) employed the syn conformer to form chiral tweezer complexes of diamines; (iv) studied the solvent-, temperature-and phase-dependence of the effects; and (v) measured thermodynamic parameters for the coordination and switching processes. 155,[188][189][190][191][192][193][194][195][196][197][198][199][200][201][202] In addition, absolute configuration assignment was possible. [203][204][205][206] The metal ion in the OEP rings was Zn(II) in most cases, either the Zn 2 or the H 2 /Zn complex, but Mg(II) and Fe(III) were also used.…”
Section: A Host-guest Interactions and Supramolecular Chemistrymentioning
confidence: 99%